Performance Evaluation of a Salivary Amylase Biosensor for Stress Assessment in Military Field Research. Issue 3 (19th January 2015) - Peng, Henry T.; Savage, Erin; Vartanian, Oshin; Smith, Shane; Rhind, Shawn G.; Tenn, Catherine; Bjamason, Stephen
Abstract : Background: A convenient biosensor for real‐time measurement of biomarkers for in‐field psychophysiological stress research and military operations is desirable. We evaluated a hand‐held device for measuring salivary amylase as a stress marker in medical technicians undergoing combat casualty care training using two different modalities in operating room and field settings. Methods: Salivary amylase activity was measured by two biosensor methods: directly sampling saliva with a test strip placed under the tongue or pipetting a fixed volume of precollected saliva onto the test strip, followed by analyzing the sample on the strip using a biosensor. The two methods were compared for their accuracy and sensitivity to detect the stress response using an enzyme assay method as a standard. Results: The measurements from the under‐the‐tongue method were not as consistent with those from the standard assay method as the values obtained from the pipetting method. The under‐the‐tongue method did not detect any significant increase in the amylase activity due to stress in the operating room ( P > 0.1), in contrast to the significant increases observed using the pipetting method and assay method with a significance level less than 0.05 and 0.1, respectively. Furthermore, the under‐the‐tongue method showed no increased amylase activity in the field testing, while both the pipetting method and assay method showed increased amylase activity in the same group ( P < 0.1). Conclusion: The accuracy and consistency of the biosensors need to be improved when used to directly measure salivary amylase activity under the tongue for stress assessment in military medical training.